Kemampuan Kinerja Keuangan dan Produksi Berbasis Green Economy dalam Peningkatan Pendapatan Resmil Desa Pulogading - Alfia Indriyanti; Anisa Sains Kharisma; Yenny Ernitawati; Nasiruddin; Amelia Sholeha (Journal of Accounting and Finance (JACFIN), 2020)
Rice milling is a meeting center between production, post-harvest, processing and marketing of grain/rice so that it is an important link in the national rice supply which is required to be able to contribute to the provision of rice, both in terms of quantity and quality to support national food security. This study aims to identify which officials have done and have not done the concept of green economy and how it affects official performance. This research method uses quantitative data types and the data sources used are primary data in the form of respondents' perceptions. The samples taken were 5 rice mills located in Pulogading village with 50 respondents. there are two data source collections carried out in the rice official, namely primary data and secondary data. This study used sampling with the accidental sampling method, which is a sampling method by identifying the general character of the research object. The results of this study showed a production variable (X1) to an increase in income (Y) of the production variable of -0.279 and a negative sign. This shows that there is a decrease in production in increasing income, which can increase the variable increase in income by 0.279. Meanwhile, the company's performance variable (X2) to the increase in revenue (Y) of the official policy variable was 0.748 and marked positive. This shows that there is an increase in employee awareness of responsibility for their work in the officialdom.